Toxicity of Chrysanthemum cinerariaefolium (Trev.) inflorescence on GUPPY. Poecilia reticulata (Peter). - Pechueco, Sheryll T
Chrysanthemum cinerariaefolium, or Pyrethrum, is an indigenous plant in Asia cultivated for its dry inflorescence. The acrive insecticidal constituents of pyrethrum flowers, pyrethrins, has minimal toxicity to higher animals making it an excellent insect deterrent. This study aimed (1) to find out whether C. cinerariaefolium could also be an effecient fish toxicant against Poecilia reticulata which is a common nuisance fish in freshwater and brackishwater ponds and (2) to determine the median lethal concentration (LC50) of pyrethrum powered inflorescence on P. reticulata., The toxic effect of Chrysanthemum cinerariaefolium powdered inflorescence on Poecilia reticulata was studied for 96 hours. Three replicates were made with the test animals exposed to 0 (control), 250, 500, 750 and 1000 mg/L concentrations of the toxicant. The data gathered includes the number of dead fish every 12 hours and the LC50. Physico-chemical parameters such as pH, temperature and dissolved oxygen were monitored. The percent mostality of the fish was statistically analyzed using the one-way analysis of variance (ANOVA), and significant results were further analyzed using the Duncan's Multiple Range Test (DMRT). (p)Results showed that there was a significant difference in the effect of various concentrations on fish mortality. Concentrations 500, 750, and 1000 mn/L were significantly lethal on the fish. the computed 96-hour LC50 was 507.76 mg/L with 6.10-6.40 95 confidence interval. Highest percent mortality was observed in 1000 mg/L. Physico-chemical parameters were found to be within tolerable range for the fishes. (CORRECTION: LC50)